Preface: THE LANGUAGE OF PANDEMICS - Daniele, Franca (European Scientific Journal, ESJ, 2020)
ESJ Special Edition 10 years European Scientific Journal, ESJ Topic: The language of Pandemics Guest Editor: Franca Daniele, MD Department of Medical, Oral and Biotechnological Sciences “G. d’Annunzio” University – Chieti-Pescara, Italy